Cash Turnover, Debt to Asset Ratio, Current Ratio dan Net Profit Margin terhadap ROE Perusahaan Konstruksi yang Terdaftar di BEI - Surti N. Sihombing; Supra Felix Sianipar; Albert Jonatan Taruli Situmorang; Jessi Charina Sembiring (IPM2KPE, 2022)
ABSTRACT This study aims to analyze the effect of Cash Turnover, liabilities on assets, current ratios, and net profit margins on the return on capital of construction companies listed on the BEI. This research method is quantitative, because the data used is numerical. The population of this survey reached 18 construction companies listed on the Indonesia Stock Exchange. The survey sample used in the form of financial statements of 10 construction companies listed on the IDX in 2016 to 2020. The type of data used in this research activity is secondary data, which was taken through the IDX official website (www.idx.co.id). The results show that the results of the T test are, a) the Cash Turnover variable has a t-count value of 3.279 > 2.026 and a significance value of 0.001 <0.05: b) the Debt to Assets Ratio variable has a t-count value of 5.348 > 2.026 and a significance value of 0.002 <0 ,05; c) the Current Ratio variable has a t value of - 0.424 < 2.026 and a significance value of 0.674 > 0.05; d) the Net Profit Margin variable has a t-count value of 1.636 < 2.026 and a significance value of 0.110 > 0.05. Also, the results of the F test show the calculated F value (24.172)>F table (2.69) with a significance value of <0.05. Conclusions, a) Cash Turnover (CT) has a significant effect on the value of companies in the Construction industry listed on the IDX in 2016-2020; b) Debt To Equity Ratio (DER) has a significant effect on the value of companies in the Construction industry listed on the IDX in 2016-2020; c) Current Ratio (CT) does not affect the value of companies in the Construction industry listed on the IDX in 2016-2020; d) Net Profit Margin (NPM) has no effect on the value of companies in the Construction industry listed on the IDX in 2016-2020. Keywords: Cash Turnover, Debt to Asset Ratio, Current Ratio, Net Profit Margin Return on Equity